2007
DOI: 10.1111/j.1398-9995.2007.01375.x
|View full text |Cite
|
Sign up to set email alerts
|

Basement membrane thickening and clinical features of children with asthma

Abstract: Basement membrane thickening has been known to be present in children with asthma. In addition, we report an association between BM thickness and sex, FEV(1)/FVC, total IgE, and the presence of IgE specific to D. pteronyssinus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 29 publications
1
31
0
Order By: Relevance
“…Similar to the findings in adult asthma patients, the thickening of RBM was present in children with severe asthma. Kim et al [25] also found basement membrane thickening in children with asthma. Cokugras et al [21] studied 10 moderate asthmatic children with a mean disease duration of 4.8 years, who were treated with sodium cromoglycate for 2.0 years and had received inhaled steroids and bronchodilators for 8 months.…”
Section: Review Articlementioning
confidence: 92%
“…Similar to the findings in adult asthma patients, the thickening of RBM was present in children with severe asthma. Kim et al [25] also found basement membrane thickening in children with asthma. Cokugras et al [21] studied 10 moderate asthmatic children with a mean disease duration of 4.8 years, who were treated with sodium cromoglycate for 2.0 years and had received inhaled steroids and bronchodilators for 8 months.…”
Section: Review Articlementioning
confidence: 92%
“…A key feature in the pathogenesis of asthma is chronic airway inflammation, characterized by the presence of inflammatory cells and the release of inflammatory mediators in the airways (2). Airway inflammation can be detected by several methods such as bronchial biopsy, bronchoalveolar lavage or induced sputum (3). However, due to their invasive character or low practical applicability, these methods are not suitable for use in young children or in large study populations.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, however, even in mild recently diagnosed asthma or in childhood asthma, significant airway remodelling can already be observed, although more needs to be known with regard to the reversibility of some of the changes at this early stage [13][14][15].…”
Section: What Are the Remaining Questions?mentioning
confidence: 99%